Concord patterns with collective nouns in Hong Kong English. With illustrative material from the International Corpus of English (Hong Kong component) - Wong, May Lai-Yin (Linguistik Online, 2009)
This corpus-based study reports on both a quantitative and qualitative account of the use of collective nouns in Hong Kong English, with particular reference to subject-verb agreement/concord patterns. Singular concord was found to be the preferred pattern among thirty-five collective nouns under interrogation in the ICE-HK corpus. It is argued that the preference for singular concord serves as a signal that Hong Kong English might be less conservative than British English in converging towards the norm of using singular concord with collective nouns across the globe.